Apakah Layanan Beli Sekarang, Bayar Nanti Membentuk Perilaku Keuangan Mahasiswa? Bukti dari Penggunaan Shopee PayLater dan Literasi Keuangan di kalangan Mahasiswa Pendidikan Ekonomi - Saragih, Gresya Jahnkia; Rosmiati, Rosmiati; Ramalia, Aminah (Magister Ilmu Akuntansi Universitas Jambi, 2026)
The problem in this research is the increasing development of digital financial services such as Shopee PayLater, which makes it easier for students to make credit purchases. This convenience has the potential to impact financial management, especially in managing expenses and financial planning. Furthermore, the level of financial literacy also plays a significant role in determining an individual's ability to manage finances wisely. This study aims to analyze the effect of Shopee PayLater usage and financial literacy on the financial management of Economics students, class of 2023-2024, at Jambi University. The research method used in this study is a quantitative descriptive method with data collection through filling out a questionnaire. The data analysis technique used is multiple linear regression analysis with the help of SPSS. The results show that partially, the use of Shopee PayLater has no significant effect on financial management. Meanwhile, financial literacy has a significant effect on student financial management. This study shows that the higher the level of financial literacy possessed by students, the better their ability to plan, organize, and control their personal finances.